111k views
1 vote
Which of the following is the correct factored form of the given equation?

4x^2 - 11x + 6 = 0

(2x + 3)(2x + 2) = 0
(2x - 3)(2x - 2) = 0
(4x - 3)(x - 2) = 0

2 Answers

1 vote


image

User Mike Tunnicliffe
by
5.6k points
3 votes

Answer: The correct option is (C)
(4x-3)(x-2)=0.

Step-by-step explanation: We are given to select the correct factored form of the following quadratic equation.


4x^2-11x+6=0

To do so, we need to factorize the left hand side of the above equation.

We have


4x^2-11x+6=0\\\\\Rightarrow 4x^2-8x-3x+6=0\\\\\Rightarrow 4x(x-2)-3(x-2)=0\\\\\Rightarrow (4x-3)(x-2)=0.

Therefore, the correct factored form of the given equation is


(4x-3)(x-2)=0.

Thus, (C) is the correct option.

User Alex Kolarski
by
5.4k points